Abusive Head Trauma and a Delay in Presentation for Care. Issue 1 (15th July 2020) - Kennedy, Juliana M.; Ma, Jihyun; Lyden, Elizabeth R.; Haney, Suzanne B.
Abstract : Objectives: Abusive head trauma (AHT) is the leading cause of death from trauma in children less than 2 years of age. A delay in presentation for care has been reported as a risk factor for abuse; however, there has been limited research on this topic. We compare children diagnosed with AHT to children diagnosed with accidental head trauma to determine if there is a delay in presentation. Methods: We retrospectively studied children less than 6 years old who had acute head injury and were admitted to the pediatric intensive care unit at a pediatric hospital from 2013 to 2017. Cases were reviewed to determine the duration from symptom onset to presentation to care and the nature of the head injury (abusive vs accidental). Results: A total of 59 children met inclusion criteria. Patients who had AHT were significantly more likely to present to care more than 30 minutes after symptom onset ( P = 0.0015). Children who had AHT were more likely to be younger (median, 4 vs 31 months; P < 0.0001) and receive Medicaid ( P < 0.0001) than those who had accidental head trauma. Patients who had AHT were more likely to have a longer length of stay (median, 11 vs 3 days; P < 0.0001) and were less likely to be discharged home than patients who had accidental head trauma (38% vs 84%; P = 0.0005). Conclusions: Children who had AHT were more likely to have a delayed presentation for care as compared with children whose head trauma was accidental. A delay in care should prompt clinicians to strongly consider a workup for abusive injury.